Climate policies and induced technological change: Which to choose the carrot or the stick? - Snorre Kverndokk; Knut Einar Rosendahl; Thomas F. Rutherford (University of Oslo, Department of Economics, 2001)
Policies to reduce emissions of greenhouse gases such as CO2 will affect the rate and pattern of technological change in alternative energy resources and other production processes. Imperfections in markets for non-polluting technologies imply that a decentralised economy does not deliver a socially optimal outcome, and this could justify policy interventions such as subsidies. This paper considers the welfare effects of technology subsidies as part of a carbon abatement policy package. We argue that the presence of spillovers in alternative energy technologies does not necessarily imply that subsidy policies are welfare improving. We illustrate this point in the context of a general equilibrium model with two forms of carbon-free energy, an existing “alternative energy” which is a substitute for carbon-based fuels, and “new vintage energy” which provides a carbon-free replacement for existing energy services. Subsidisation of alternative energy on the grounds of spillover effects can be welfare-worsening if it crowds-out new vintage technologies.
Keywords: D58; H21; O30; Q42; 330; Induced technological change; Climate change policies; Policy instruments; Computable general equilibrium models; Klimaschutz; Wohlfahrtseffekt; Umwelttechnik; Förderung regenerativer Energien; Theorie